Immune Control of Animal Growth in Homeostasis and Nutritional Stress in Drosophila - P, Preethi; Tomar, Ajay; Madhwal, Sukanya; Mukherjee, Tina (Frontiers in Immunology, 2020)
This study explores the importance of innate immune cells in animal growth control during homeostasis and in conditions of dietary sugar stress. We find that Drosophila larvae lacking blood cells eclose as smaller adults. Moreover, when exposed to diet with high dietary sugar these animals show further retardation in adult growth. Contrarily, larvae carrying activated macrophages as a consequence of expression of a constitutively active form of PDGF-VEGF like receptor (Pvractivated) show recovery from the high sucrose-induced growth defect. Implying, a necessary role for innate immune cells in growth control and their sufficiency in moderating it in conditions of excessive dietary sucrose stress. Mechanistically, our investigations reveal a role for the myeloid like-immune cells in controlling secretion of insulin from insulin producing cells (IPCs) of the larval brain and its sensitivity in peripheral tissues in both regular and dietary sugar stress states. Thus revealing an integral role for immune cells in synergizing nutrient availability, insulin signaling with systemic metabolic homeostasis and animal growth early in Drosophila development. Overall, evidences across systems highlight connect between nutrient availability on animal growth and development of an effective immune system. Our findings reveal the underlying capacity of the immune cells that defines this connect alluding to possibilities that may be broadly conserved across higher mammalian systems.